Contribution of Regional Taxes and Levies in Supporting Pad in the Surabaya City Government - Suparman Suparman; Aris Sunarya; Sarwani Sarwani (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This study explores the contribution of regional taxes and levies to Regional Original Revenue (PAD) in Surabaya City and their role in fostering fiscal independence within the framework of regional autonomy. Employing a descriptive qualitative approach, data were collected from the Surabaya City Regional Revenue Agency and relevant local government offices, complemented by secondary sources such as regulatory documents and literature on regional finance. The data analysis process followed McNabb’s (2002) framework, which consists of categorization, interpretation, generalization, testing alternative perspectives, and refining theoretical insights. The findings reveal that PAD acts as a crucial financial backbone for the implementation of regional autonomy, with taxes and levies serving as the primary contributors. On average, these sources accounted for 89.08% of the total PAD during the 2021–2024 period. The growth trend observed is driven by several factors, including the presence of a comprehensive legal and regulatory framework, diversification of tax types and structures, adequate institutional and human resource capacity, as well as increasing public awareness of tax obligations. Although there was a temporary decline in proportional contribution in 2023, overall tax and levy collections exceeded their targets, underscoring their vital role in supporting government administration and regional development programs. This study emphasizes the need for strengthening regulatory frameworks, enhancing administrative capacity, encouraging greater community participation, and optimizing the use of digital technologies to improve efficiency in revenue collection. These strategies are essential to reduce reliance on central government transfers and to promote greater fiscal independence for Surabaya City.